„Wierszem można odkorkować duszę” – o sacrum w twórczości Wacława Oszajcy - Popielarz-Zajdel, Ewelina (Dydaktyka Polonistyczna, 2020)
Wacław Oszajca is a Polish Jesuit, journalist, poet and publicist. His work is mainly focused around Christianity related matters. A Jesuit uses the category of the sacred as a synonym for what is saint. It defines the sacred as a force that puts together the chaos of everyday life, it is the Absolute, thanks to which we can reach faith in the infinity of the world. Oszajca tries to provoke the reader into thinking about the presence of the sacred in his life and shows that the division into the sacred and the profane should be removed. His work is a proof of adoration of everyday life and faith in a merciful but righteous God. When writing, he often uses contrasts and paradoxes, but above all his poetry is full of humor and joy.